Revision of the Genus Metaleptea Brunner von Wattenwyl (Orthoptera; Acrididae; Hyalopterygini) - Donato, Mariano Humberto (2000)
In this study Metaleptea is redescribed based on characters from the external morphology and genitalia. The two known subspecies proposed by Rehn (1944) for M. brevicornis (M. b. brevicornis and M. b. adspersa) are considered separate species based on characters found in the male genitalia and female subgenital plate. To analyze if these species show geographic variation in body size, measurements of morphological characteristics were made on adults collected from different localities over the known distributions. Multivariate analyses results showed that there is no evidence of direct relationship between the body size variation and the geographic distribution of specimens, although the species are highly variable in size and color patterns.